Building urban local governance fiscal autonomy through property taxation financing option - Aluko, Bioye Tajudeen (International Journal of Strategic Property Management, 2010)
The continued productivity of urban economies depends upon the provision of urban infrastructure and social services. And, a large share of the service‐provision role is conventionally assigned to local government as tastes and preferences vary among individuals and communities. This requires financing the public expenditures and, although, there are other sources of revenue, taxation is very central to effective and efficient service‐delivery. The paper, therefore, examines the role of property taxation in this regard with a view to promoting and building urban local governance autonomy in cities of developing world. The paper also examines the essentials of a good property tax and problems of its administration in Africa urban local governments. Consequently, a prima facie case for property tax reforms is made in order to improve the revenue‐generating potentials of the tax. More importantly, the paper concludes that the real challenge towards sustainable fiscal autonomy for urban local governance in developing countries is to rally all actors or stakeholders at the policy planning and administration of property tax stages. This will ensure effective mobilization of all for the success of such tax.First Published online: 18 Oct 2010